2018
DOI: 10.1016/j.ejpal.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

To Confront Versus not to Confront: Women’s Perception of Sexual Harassment

Abstract: A B S T R A C TCurrent research has postulated that sexual harassment is one of the most serious social problems. Perceptions of sexual harassment vary according to some factors: gender, context, and perceiver's ideology. The strategies most commonly used by women to cope with harassment range from avoiding or ignoring the harasser to confronting the harasser or reporting the incident. The aim of this study was to explore women's perception of sexual harassment, and to assess the implications of different vict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 36 publications
4
41
0
3
Order By: Relevance
“…First of all, the small number of studies published between 2005 and 2018 in scientific journals analysing the relationship between sexism and cognitive, emotional, attitudinal, and behavioural variables involved in adolescent relationships should be noted; only 20 articles were found. Sexist attitudes were linked to major social problems, such as intimate partner violence (Bringas-Molleda et al, 2017;García-Díaz et al, 2016;Herrera, Herrera, & Expósito, 2018;López-Cepero, Rodríguez-Franco, Rodríguez-Díaz, & Bringas, 2013;López-Ossorio et al, 2018;Moyano, Monge, & Sierra, 2017) or risky sexual behaviours (Kocken, Van-Dorst, & Schaalma, 2006;Nanda, Schuler, & Lenzi, 2013) in adult population. Therefore, it is contradictory to find little research analysing these relationships in adolescent population, since adolescence is a time when gender identities (Walker & Barton, 1983) that influence affective and love relationships begin to emerge (Duque, 2006;Sanpedro, 2005) and when the first sexual intercourse takes place (Ramiro-Sánchez, Ramiro, Bermúdez, & Buela-Casal, 2018a;Teva, Bermúdez, Ramiro, & Ramiro-Sánchez, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…First of all, the small number of studies published between 2005 and 2018 in scientific journals analysing the relationship between sexism and cognitive, emotional, attitudinal, and behavioural variables involved in adolescent relationships should be noted; only 20 articles were found. Sexist attitudes were linked to major social problems, such as intimate partner violence (Bringas-Molleda et al, 2017;García-Díaz et al, 2016;Herrera, Herrera, & Expósito, 2018;López-Cepero, Rodríguez-Franco, Rodríguez-Díaz, & Bringas, 2013;López-Ossorio et al, 2018;Moyano, Monge, & Sierra, 2017) or risky sexual behaviours (Kocken, Van-Dorst, & Schaalma, 2006;Nanda, Schuler, & Lenzi, 2013) in adult population. Therefore, it is contradictory to find little research analysing these relationships in adolescent population, since adolescence is a time when gender identities (Walker & Barton, 1983) that influence affective and love relationships begin to emerge (Duque, 2006;Sanpedro, 2005) and when the first sexual intercourse takes place (Ramiro-Sánchez, Ramiro, Bermúdez, & Buela-Casal, 2018a;Teva, Bermúdez, Ramiro, & Ramiro-Sánchez, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding hypothetical scenarios, although they have been used extensively because of their usefulness to vary specific features while holding other features constant (e.g., Hammock et al, 2015;Katz et al, 2007;Tamborra et al, 2014) and afforded this advantage in making sexual claims, participants' responses in these situations could differ from real-life responses. Furthermore, previous experience of sexual violence and general attitudes towards violence against women (e.g., rape myths, sexist ideology) should be considered in future studies, since past research has found these attitudes are crucial for understanding reactions and behaviours towards victims and aggressors (e.g., Herrera et al, 2014Herrera et al, , 2018. An additional limitation is that participants were from the general population, so that caution should be taken when generalising the results for professional or applied practice.…”
Section: Article In Pressmentioning
confidence: 99%
“…Although there is an inherently subjective component, sexual harassment measures vary based on the extent to which they are subjective (i.e., psychological, sex‐based) or more objective (i.e., legal, behavioral) in focus (O'Leary‐Kelly et al., ). Subjective measures (i.e., psychological, sex‐based) focus on whether the target of an act perceives it to be sexual harassment, which is impacted by individual differences and situational factors (Herrera, Herrera & Expósito, ), whereas more objective measures (i.e., legal, behavioral), although still somewhat subjective, assess the occurrence of specific, offensive or unwanted sexual harassment behaviors rather than an individual's reaction to it (O'Leary‐Kelly et al., ). In the EEOC's Study of Harassment in the Workplace (Feldblum & Lipnic, ), 25% of women report being sexually harassed when asked simply whether they experienced “sexual harassment,” but this number increases to 40% when using a behavioral measure because it captures incidents of offensive, unwanted sexually based behaviors (i.e., sexual harassment) that may not always be labeled or reported as such (Bowes‐Sperry & O'Leary‐Kelly, ).…”
Section: Antecedents Of Sexual Harassmentmentioning
confidence: 99%